Geotechnical Indications of Bille Communnity in Niger Delta (Global Journal of Science Frontier Research, 2018)
The study area which is situated Morphologically within the Salt Water / Mangrove swamp Zone, is underlain by thick volume of clay with low Cu value of 14kpa and high Coefficient of Compressibility value. This results in large settlement observation and foundation failures of structures with high columns loads. Thus, Deep foundation is recommended for such structures . Soil Lithology reveals a medium dense Sandy layer (phi=>30) at an average depth >15m and Uniformity Coefficient indicating the sand as well graded. Pile load calculations indicates working loads < 300KN within diameter of 0.3m-0.45m at depths of 15m. Settlement calculations reveals expected settlement values of individual piles lower the allowable values.
Keywords: component; deep foundation; bearing capacity; foundation failures; niger delta; settlement